Growing up with the town : family & community on the Great Plains - Schwieder, Dorothy, 1933-2014 (University of Iowa Press, 2002)
In this unusual blend of chronological and personal history, Dorothy Hubbard Schwieder combines scholarly sources with family memories to create a loving and informed history of Presho, South Dakota, and her family's life there from the time of settlement in 1905 to the mid 1950s.